Features of formation of land plots construction and maintenance of buildings of educational establishments - Kustovska, O.; Kovalenko, V. (Land Management, Cadastre and Land Monitoring, 2020)
In the article the normative-legal base on formation of land plots for construction and maintenance of buildings of educational institutions, in particular, it analyses the Law of Ukraine «About education» from 05.09.2017 year. It is established that the ability to obtain the right of permanent use of land granted to all without an exception educational institutions regardless of their form of ownership (previously, this right could only acquire higher education institutions), transfer for permanent use to the educational institutions of the land on which are located buildings and structures of such institutions is: the academic building, laboratories, dormitories, libraries and such. Also decided on the number of subjects in educational institutions include legal entities of public or private law the main activity of which is educational activities.The study was conducted on the example of the development of the land for teaching and Educational complex «Preschool educational establishment - General educational school No. 11» city of Tokmak of Zaporizhzhya region. Evaluated current use of lands of the city of Tokmak.We also study the category of land that can be transmitted to educational institutions for permanent use, in particular, of agricultural land and defense, as for other categories of land, the legislation does not contain mandatory rules as to the impossibility of their transfer for permanent use to educational institutions. Justified the procedure of formation of land plots for construction and maintenance of buildings of educational institutions.Keywords: land, construction and maintenance of buildings of educational institutions, institutions of higher education, permanent use.